A Study of Electrochemical Measurements Under Microemulsion Condition Corrosion - Muzir, Nur Ashila Nadhirah (IRC, 2020)
Corrosion is one of the main integrity threats in crude oil pipeline transportation. Accurate online corrosion monitoring is critical to the effective implementation of corrosion mitigation method. Current electrochemical methods of linear polarization resistance (LPR) relies on high conductivity of interfacial solution. The challenge in measurement is due to microemulsion condition has low conductivity of interfacial solution which affect the accuracy of the LPR. The study was undertaken to evaluate the effect of microemulsion on the accuracy of linear polarization resistance (LPR) and electrochemical impedance spectroscopy (EIS) electrochemical measurement. The experimental work consists of using mild steel as the working electrode for LPR and EIS test.